Characterization and distribution of putative 5-ht7 receptors in guinea-pig brain. - To, Z. P. (1995)
1. In the presence of (-)-cyanopindolol (1.0 microM) and sumatriptan (1.0 microM), 0.5 nM [3H]-carboxamidotrytamine ([3H]-5-CT) labelled a single population of receptors in guinea-pig cerebral cortex membranes. 2. 5-HT-displaceable binding was rapid, saturable and reversible. A high affinity binding site was characterized both by equilibrium saturation (Kd = 0.76 +/- 0.28 nM; Bmax = 68.1 +/- 26.7 fmol mg-1 protein) and kinetic (Kd = 0.18 +/- 0.05 nM) analysis. The pharmacological profile of this site was similar to the profile obtained in transfected CHO-K1 cells expressing guinea-pig 5-ht7 receptors. 3. Autoradiographic analysis revealed a discrete localization of binding sites in guinea-pig brain, with the highest density of sites in the medial thalamic nuclei and related limbic and cortical regions. Moderate levels of binding were detected in sensory relay nuclei, substantia nigra, hypothalamus, central grey and dorsal raphe nuclei. This distribution corresponded to that observed using in situ hybridization with [35S]-UTP labelled riboprobes complementary to mRNA encoding the guinea-pig 5-ht7 receptor. 4. In conclusion, under appropriate conditions, [3H]-5-CT labelled a single population of saturable binding sites that corresponded to an endogenous 5-ht7 receptor in guinea-pig brain. The distribution of 5-ht7 receptors in thalamocortical and limbic brain regions suggests a role for these receptors in sensory and affective behaviours.